2016
DOI: 10.21276/irjps.2016.3.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Rp-HPLC Method for the Determination of Nitazoxanide and Ofloxacin in Combined Pharmaceutical Dosage Forms

Abstract: ABSTRACT:A simple, rapid, specific and reproducible reverse phase HPLC method was developed and validated for the simultaneous separation and estimation of the Nitazoxanide and Ofloxacin from the commercially available tablet dosage form. The chromatography was carried out using a combination of 0.863% (w/v) ammonium dihydrogen orthophosphate buffer and Acetonitrile (45:55 ratio (v/v)) at a flow rate of 1.0 ml/min and was monitored at 240 nm wavelength. The method was statistically validated by the study of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Harika M et al, 37 developed a method for estimating nilotinib by using RP-HPLC in bulk and pharmaceutical dosage form. The separation of analyte was carried out on C18 analytical column (250 × 4.6 mm, 5 µ) with isocratic mode.…”
Section: Fig 2: Mechanism Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Harika M et al, 37 developed a method for estimating nilotinib by using RP-HPLC in bulk and pharmaceutical dosage form. The separation of analyte was carried out on C18 analytical column (250 × 4.6 mm, 5 µ) with isocratic mode.…”
Section: Fig 2: Mechanism Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…CFX is official in British Pharmacopeia (BP), European Pharmacopeia (EP) [1,2] and United States Pharmacopeia (USP) [8], both of them includes HPLC Method for its estimation. Literature review revealed that various analytical methods have been described for the determination of CFX including colorimetric and spectrophotometric [9][10][11][12][13][14][15][16][17][18][19][20][21][22], thin layer chromatography (TLC) [23][24][25][26], capillary electrophoresis [27][28][29], high performance liquid chromatography (HPLC) [30][31][32][33][34][35][36][37][38][39] and electrochemical methods [40][41][42][43] have been developed for the estimation of CFX in pure or in dosage forms. SDM is official in BP, EP [1,2] and United States Pharmacopeia (USP) [8], which includes direct titration for estimation of SDM.…”
Section: Cfx; Is Chemically Known As (6r7r)-7-[[(z)-2-(2-aminothiazol...mentioning
confidence: 99%
“…Compound which is more hydrophobic will be retained longer on the column than lesser hydrophobic one, based on the hydrophobicity they get separated. Organic and aqueous phases are the two components which are used as mobile phase [3]. As per "World Health Organization" reservation, INH is one the front line agent for the treatment of tuberculosis and INH pertains to the category of nucleoside reverse transcriptase inhibitor [4], with aqueous solubility of 140 mg/ml [5].…”
Section: Introductionmentioning
confidence: 99%